The interrelation of parental alcohol use, parental practices, and binge drinking among secondary and high school students: analysis of a national survey - Mondragón Gómez, Raquel; Villatoro Velázquez, Jorge A.; Medina-Mora Icaza, Maria Elena; Lucio y Gómez Maqueo, Emilia (Frontiers in Public Health, 2025)
IntroductionUnderstanding the role of parenting practices and their potential interaction effect between parental and adolescent alcohol use is critically important for informing and developing interventions aimed at preventing binge drinking among adolescents.ObjectiveTo evaluate the effect of parental problematic alcohol consumption and parenting practices on alcohol use among students, using a nationally representative sample of adolescents in Mexico.MethodologyA secondary analysis was conducted using the National Survey on Drug Use among Students, based on data from 114,364 middle and high school students. A multivariable analysis of prevalence ratios (PR) was conducted using generalized linear models (GLM) with log-link and binomial distribution. From this global analysis, the nlcom command was used to compare parenting practices within each category of parental problematic alcohol use.ResultsThe results indicated a higher risk of binge drinking among students who reported a father with problematic alcohol use and perceived negative supervision or lack of parental involvement (PR = 1.63 [95% CI: 1.43–1.86]; PR = 1.36 [1.19–1.56], respectively); among those who reported problematic use in both parents and perceived negative supervision (PR = 1.32 [95% CI: 1.06–1.64]); similarly, among those whose parents did not report problematic use, but perceived negative supervision or negligent parenting practices (PR = 1.50 [95% CI: 1.41–1.59]; PR = 1.13 [95% CI: 1.04–1.24], respectively), and when they perceived no parental involvement or encouragement (PR = 1.44 [95% CI: 1.35–1.53]; PR = 1.12 [95% CI: 1.04–1.24], respectively).DiscussionThe findings highlight the importance of developing and strengthening prevention efforts that promote positive parenting practices and enhance parents’ understanding of how their alcohol use affects their children’s behavior.